Inclusion controlled lanthanide-imidazolium functionalised carboxylate complexation - Ling, I.; Alias, Yatimah; Skelton, B.W.; Raston, C.L. (Royal Society of Chemistry, 2012)
Imidazolium functionalized carboxylic acid forms a multi-component material with p-sulfonatocalix[4]arene and aquated lanthanide ions, stabilising dinuclear metal complexes for Y(3+) and Gd(3+). These have the simplest binding of two bridging carboxylates between the two metal centres (Y(3+)), or the same arrangement along with the simplest binding of one carboxylate bridging two metal ions for the larger metal ion (Gd(3+)).